What have we learned about cues to deception? A survey of expert opinions - Luke, Timothy J. (Psychology, crime & law, 2025)
Researchers have accumulated a substantial body of empirical work studying observable behaviors that might distinguish truth tellers from liars – that is, cues to deception. We report a survey of N = 50 deception cue experts – active researchers on deception – who provided their opinions on three issues: (1) What cues distinguish between truthful and deceptive statements? (2) What moderators influence the magnitude and direction of cues to deception? (3) What explanatory mechanisms of deception cues are best supported by research? The experts displayed agreement on few issues. Expert opinion on cues to deception, potential moderators, and explanatory mechanisms is mixed and often conflicting. The single issue on which more than 80% of experts agreed was that gaze aversion is not generally diagnostic of deception. This lack of consensus suggests that substantial work remains to be done before broad agreement can be established. It follows that any practical recommendation advocating the use of a specific deception cue cannot be widely representative of expert opinion.